The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1177/03635465000280041901
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of the Semitendinosus Tendon Harvested for Anterior Cruciate Ligament Reconstruction: Evaluation Using Ultrasonography

Abstract: In a prospective study, 40 consecutive patients who underwent anterior cruciate ligament reconstruction with doubled semitendinosus and gracilis tendon autografts were examined pre- and postoperatively by ultrasound to investigate the anatomy of the donor site before and after the harvest of the tendons. The patients underwent ultrasonography at 2 weeks and 1, 2, 3, 6, 12, 18, and 24 months postoperatively. A total of 298 postoperative sonographic evaluations were performed. The semitendinosus tendon was image… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
106
2
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 116 publications
(119 citation statements)
references
References 23 publications
7
106
2
4
Order By: Relevance
“…If only the ST ST semitendinosus tendon was harvested with an intact G tendon, neotendon developed in 18 (72 %) cases, and then the insertion site was mostly below the joint line but above previous pes anserinus site, in 15 (83.3 %) of the legs. Our ultrasound findings are in agreement with findings from imaging studies in which the regenerated ST tendon seemed to insert more proximally on the gastrocnemius fascia rather than on the tibia, as does the native ST tendon [5,6,[17][18][19][20][21]. This different insertion pattern of the regenerated tendon could explain how it acts mainly as a flexor muscle rather than as a flexor and internal rotator [22][23][24].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…If only the ST ST semitendinosus tendon was harvested with an intact G tendon, neotendon developed in 18 (72 %) cases, and then the insertion site was mostly below the joint line but above previous pes anserinus site, in 15 (83.3 %) of the legs. Our ultrasound findings are in agreement with findings from imaging studies in which the regenerated ST tendon seemed to insert more proximally on the gastrocnemius fascia rather than on the tibia, as does the native ST tendon [5,6,[17][18][19][20][21]. This different insertion pattern of the regenerated tendon could explain how it acts mainly as a flexor muscle rather than as a flexor and internal rotator [22][23][24].…”
Section: Discussionsupporting
confidence: 89%
“…The process of regeneration investigated by ultrasonography in our study and suggested by the sonography findings in the other studies confirmed that fibrillary tendon-like tissue seems to fill the site originally occupied by the ST tendon. Moreover, sonography showed the trend of healing of the donor defect with hypertrophic tendinous tissue seen up to six months after surgery, while the ultrasound structure and measurements are consistent with normal tendon 12 to 18 months after surgery [19].…”
Section: Discussionmentioning
confidence: 64%
“…It should also be considered that ST tendon regeneration after ACLR may take approximately 18 months (Papandrea, Vulpiani, Ferretti, & Conteduca, 2000) and may not occur at all in 10 to 50 % of patients (Konrath et al, 2016;Nomura et al, 2015;Snow et al, 2012). Contrary to our hypothesis, there were no significant differences in eccentric knee flexor strength between surgical and control limbs, although there was considerable between-subject variability.…”
Section: Discussioncontrasting
confidence: 84%
“…Even in acute cases treatment of associated injuries can be performed uneventfully. Excellent functional recovery can be due to the potential for regeneration offered by the semitendinosus and documented by imaging, functional and histological studies (6)(7)(8). Another brilliant intuition of Professor Perugia was his use of peripheral plasties in place of or to support intra-articular reconstruction.…”
Section: J Ointsmentioning
confidence: 99%